2018
DOI: 10.1042/bsr20180613
|View full text |Cite
|
Sign up to set email alerts
|

MiR-629-5p promotes colorectal cancer progression through targetting CXXC finger protein 4

Abstract: MiR-629-5p has been shown to function as a tumor promoter in some types of cancer. However, the role of miR-629-5p in colorectal cancer remains unclear. Here, the significant up-regulation of miR-629-5p in colorectal cancer tissues and cell lines was observed. Overexpression of miR-629-5p showed a positive effect on cell proliferation and migration. The enhanced miR-629-5p level also suppressed cell apoptosis and resulted in a low Bax level and a high Bcl-2 level. Further down-regulating miR-629-5p demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 24 publications
4
15
0
Order By: Relevance
“… 28 The evidence derived from our study suggested that miR-675-3p targeted CXXC4. A previous study suggested that miR-629 is able to accelerate the progression of cancer by binding to CXXC4 in colorectal cancer cells, 29 which further validates our findings that CXXC4 could be a target gene of miRNA. We also evaluated the relationship between miR-675-3p and PD-L1, which showed that GC-EV-delivered miR-675-3p not only promoted PD-L1 expression, but it also suppressed the activation of T cells in GC modeled mice.…”
Section: Discussionsupporting
confidence: 90%
“… 28 The evidence derived from our study suggested that miR-675-3p targeted CXXC4. A previous study suggested that miR-629 is able to accelerate the progression of cancer by binding to CXXC4 in colorectal cancer cells, 29 which further validates our findings that CXXC4 could be a target gene of miRNA. We also evaluated the relationship between miR-675-3p and PD-L1, which showed that GC-EV-delivered miR-675-3p not only promoted PD-L1 expression, but it also suppressed the activation of T cells in GC modeled mice.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, an in vitro assay showed that overexpression of miR-629 promoted the proliferation, migration, and invasiveness of HCC cells, while knockdown of miR-629 led to the opposite effects [18]. In colorectal cancer, miR-629 was found to be significantly upregulated in colorectal cancer tissues and cell lines, and upregulation of miR-629 enhanced cell proliferation and migration as well as suppressed cell apoptosis by directly downregulating CXXC4 [19].…”
Section: Discussionmentioning
confidence: 98%
“…MI is a second messenger of follicle-stimulating hormone (FSH) and DCI is an aromatase inhibitor in the human ovary [ 35 ]. Previous research found that PAE significantly decreased serum insulin and glucagon levels, improved insulin sensitivity and serum lipids profiles, and alleviated hepatic steatosis in Sprague-Dawley rats [ 36 ]. Therefore, we speculated that one of the possible mechanisms by which PAE improved ovarian fibrosis should be related to the reduction in androgen levels and inhibition of TGF-β1/Smads signaling pathway by improving insulin resistance.…”
Section: Discussionmentioning
confidence: 99%